The Influence of Job Satisfaction and Organizational Commitment on Organizational Citizenship Behavior (OCB) And Its Impact on Employee Performance - Wahyulia Saraswati; Edy Yulianto; Teuku Noerman (Wacana: Jurnal Sosial dan Humaniora)
This correlational research will be carried out on employees at the Secretariat General of the Ministry of Religion. The study should determine the influence between job satisfaction, organizational commitment, OCB, and employee performance. This study employed explanatory research and used a simple random sampling method. The population of this study consisted of employees at the Secretariat General of the Ministry of Religion, with certain criteria, totaling 386 people. The sample used was 197. The analysis method used was SEM-PLS, which employed both outer and inner model analysis. Data testing will be carried out using the Smart PLS software version 3. The final findings from research on job satisfaction factors and organizational commitment to organizational citizenship behavior and their impact on employee performance show five direct and two significant indirect influence channels in shaping job satisfaction—and organizational commitment to OCB so that it can impact employee performance.